Management of development of renewable energy sources - Inić Branimir P. (Tehnika, 2014)
The aim of the paper: 'Management of development of renewable energy sources is to point out the possible solutions for neutralizing the threat of energy shortages. The paper outlines major short and long term energy problems facing humanity. The increase of world human population is, inevitably, accompanied by higher energy consumption. Reserves decrease of nonrenewable energy sources like oil, gas, and coal is a major threat to maintaining current living conditions, and thus requires solutions in order to neutralize the threat. This is why the management of development of renewable energy sources is an imperative for Serbia. The paper emphasizes the use of solar energy, because the annual average of solar radiation in Serbia is about 40% higher than the European average, however, the actual use of the sun's energy to generate electricity in Serbia is far behind the countries of the European Union. Solar energy is clean, renewable, and the fact that 4.2 kilowatt-hours are received daily per square meter averaged over the entire surface of the planet, makes it an almost unused energy source, Compared to EU countries, the price of non-renewable derived energy is, on average, higher in Serbia. Taking this into consideration, the use of solar energy, as an unused resource, imposes itself as indispensable.